2011
DOI: 10.1002/hyp.8217
|View full text |Cite
|
Sign up to set email alerts
|

Characterising soil moisture in transport corridor environments using airborne LIDAR and CASI data

Abstract: Hardy, A. J., Barr, S., Mills, J., Miller, P. (2012). Characterising soil moisture in transport corridor environments using airborne LIDAR and CASI data. Hydrological Processes, 26 (13), 1925-1936Much of the world's transport networks are located on cutting and embankment earthworks. In the UK, many of these earthwork structures were constructed in the mid-19th century and are susceptible to slope instability. Instability in transport corridors tends to be triggered by an increase in pore water pressure, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…a wet , a dry , b wet , and b dry are the linear regression parameters (slope and intercept) of dry/wet edges, respectively. Based on TVDI, RSM can be related to LST min and LST max with the following equation [49,50]: (6) From Equation (6) RSM can be found as:…”
Section: Temperature Vegetation Dryness Index (Tvdi)mentioning
confidence: 99%
See 1 more Smart Citation
“…a wet , a dry , b wet , and b dry are the linear regression parameters (slope and intercept) of dry/wet edges, respectively. Based on TVDI, RSM can be related to LST min and LST max with the following equation [49,50]: (6) From Equation (6) RSM can be found as:…”
Section: Temperature Vegetation Dryness Index (Tvdi)mentioning
confidence: 99%
“…Microwave sensors have been used for SM retrieval due to the direct relationship between microwave radiation and soil dielectric, though providing a coarse spatial resolution [5]. As for indirect approaches, SM estimation from visible and infrared data is based on land surface reflectance at much higher spatial resolutions [6]. To evaluate SM estimation, there are many studies on the comparison of SM products and modeled SM on different scales [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results showed that this method performed well with limited training samples. In this work, we combined features extracted from airborne LiDAR data and hyperspectral compact airborne spectrographic imager (CASI) data [ 13 ]. For the hyperspectral CASI images, features of the normalized difference vegetation index (NDVI) and the gray-level co-occurrence matrix (GLCM) were calculated [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…LiDAR (light detection and ranging) technology was recently investigated as a remote sensing tool for soil moisture detection [20,[45][46][47][48][49]. This technique also enables highresolution terrain mapping and surface characterization [50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%